2022
DOI: 10.22207/jpam.16.3.21
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Characterization of Virulence Factors and Antibiogram of Klebsiella pneumoniae Isolates from Various Clinical Samples – A Cross Sectional Study

Abstract: K. pneumoniae is known to cause hospital and community acquired infections. It is usually associated with upper & lower respiratory infections, septicaemia, urinary tract infection, wound infections, neonatal sepsis, meningitis, and endophthalmitis. The virulence factors play a role in its existence in different environmental conditions and therefore help in establishing Klebsiella pneumoniae infection in the human body. Multi drug resistant Klebsiella pneumoniae is an increasing threat to human health. Kl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
1
0
2
Order By: Relevance
“…1). Our findings contradict those of (Hullur et al, 2022), who found that the percentage of capsule generation by Klebsiella pneumonia was 100%. The capsule is a significant virulence factor that participates in at least two harmful pathways, including direct inhibition of the host immune response and phagocytosis resistance.…”
Section: Results and Discussion Detection Of Several K Pneumonia Viru...contrasting
confidence: 99%
See 1 more Smart Citation
“…1). Our findings contradict those of (Hullur et al, 2022), who found that the percentage of capsule generation by Klebsiella pneumonia was 100%. The capsule is a significant virulence factor that participates in at least two harmful pathways, including direct inhibition of the host immune response and phagocytosis resistance.…”
Section: Results and Discussion Detection Of Several K Pneumonia Viru...contrasting
confidence: 99%
“…Our findings agreed with those of (Ramakrishnan et al,2019), who found that 44% of K. pneumonia was positive for protease. However, our findings disagreed with those of (Hullur et al,2022), who found that 90% of K. pneumonia was positive for protease production. Microbial proteases operate as virulence factors in many diseases caused by bacteria (protein breakdown).…”
Section: Fig 2: Hypermucoviscosity Test By K Pneumoniacontrasting
confidence: 99%
“…In this study, 40% of isolates were biofilm producers. Similar findings are reported by Madhavi S. Hullur et al 21 stated that 54% K. pneumoniae isolates were identified as biofilm producers. In another study, Rakesh Prasad Sah et al 22 reported that 57.4% K. pneumoniae strains were biofilm producers.…”
Section: Resultssupporting
confidence: 88%